Do you know this syndrome? Ascher´s syndrome: clinical findings of little known triad - Carolina Mendonça Gama Donato; Daniel Fernandes Melo; Juliana de Noronha Santos Netto (Sociedade Brasileira de Dermatologia, 2017)
Abstract: Ascher's syndrome consists of double lip, blepharochalasis and sometimes non-toxic thyroid enlargement. It is a rare, benign, rarely reported, and sometimes misdiagnosed condition that most often affects patients under 20 years old. The etiology remains unknown, although factors such as trauma, hormonal dysfunction and heredity have been suggested. Treatment based on surgical intervention is indicated to improve aesthetics or function. The presented case shows a patient diagnosed with Ascher's syndrome based on clinical findings such as double lip and blepharochalasis.